Maximizing Purity And Recovery Of Carbon Dioxide From Biogas By Equalized Pressure Swing Adsorption Using UiO66 Adsorbent - Tan, Wern Ke (Universiti Sains Malaysia, 2018)
High price of natural gas due to high demand and environmental issues that caused by releasing methane and carbon dioxide (greenhouse gases) from biogas make biogas upgrading necessary. In this study, UiO66 adsorbent in pressure swing adsorption (PSA) processes was selected for biogas upgrading. The UiO66 adsorbent was prepared and characterized using X-Ray Diffraction (XRD) analysis, Brunauer–Emmett–Teller (BET) Analysis, Scanning Electron Microscope (SEM) analysis, Energy Dispersive X-Ray (EDX) analysis and Particle Size Analysis. The characterization tests showed that UiO-66 was mesoporous, slit-shaped, has low BET surface area and crystalline structure. Breakthrough study was carried out on the UiO66 adsorbent with feed gas composition (30%CH4 - 70% CO2) under 3 bar. CO2 is the slightly strong adsorbed species compared to CH4 in a UiO66 adsorbent which was proven by its slightly longer breakthrough time than CH4 breakthrough time. Blowdown and adsorption time were selected based on breakthrough and saturated time and applied in PSA to obtain purity and recovery of CO2 and CH4. Maximum purity and recovery of CO2 are 82.70% and 36.24% respectively whereas maximum purity and recovery of CH4 are 38.22% and 86.92% respectively at 3.2 minutes of adsorption time and 3 minutes of blowdown time under 3 bar.